Pathways of association between husbands' migration and mental health of their wives who stay behind - Sauharda Rai; Rubina Awale; Dirgha Jibi Ghimire; Deepa Rao (Elsevier, 2023)
Background: Labor migration practices among married men have brought changes in gender roles and expectations, creating both opportunities and barriers for their wives who stay behind. When husbands migrate, their wives can experience major life events within private and public spheres. Literature on mental health suggests that important life events can induce or prevent the emergence of common mental disorders. Therefore, we aim to identify the psychosocial factors that link husbands' migration to their wives' mental health. Methods: We conducted in-depth interviews with eighteen women whose husbands left home for work and three key-informant interviews with a local health worker, non-government organization worker and a psychosocial counselor. We held two focus group discussions with psychosocial counselors and researchers working in the field of mental health and migration in Nepal. We analyzed data using thematic analysis based on the grounded theory approach. Results: We identified five salient psychosocial factors that illustrate how the migration of men may impact the mental health of their wives: 1) communication; 2) children as coping and stress-inducing agents; 3) family support and challenges; 4) migration history in the family; and 5) social acceptance of labor migration. Conclusion: We identified several psychosocial factors that explain the relationship between husbands' labor migration with their wives' mental health. These factors interact through a complex pathway that can either ease or add burden to wives' mental health.